Long-Term Survival in Nonsurgical Esophageal Cancer Patients Who Received Consolidation Chemotherapy Compared With Patients Who Received Concurrent Chemoradiotherapy Alone: A Systematic Review and Meta-Analysis - Xia, Xiaojie; Liu, Zeyuan; Qin, Qin; Di, Xiaoke; Zhang, Zhaoyue; Sun, Xinchen; Ge, Xiaolin (Frontiers in Oncology, 2021)
Background Concurrent chemoradiotherapy (CCRT) is the standard treatment for non-surgical esophageal cancer. Whether consolidation chemotherapy (CCT) following CCRT is beneficial for esophageal cancer remain controversial. We thus performed a meta-analysis to assess the necessity of CCT for inoperable esophageal cancer. Materials and methods We systematically searched PubMed, Embase, Cochrane Library, Web of science and CNKI for relevant published articles up to July 2020 comparing CCRT plus CCT against CCRT alone for non-surgical esophageal cancer (EC) patients. We analyzed hazard ratio (HR) to evaluate the time-to-event data and odds ratio (OR) to compare the treatment-related effect. Results The eleven retrospective studies contained a total of 2008 patients. Of these 2008 patients, 1018 received CCRT plus CCT and 990 received CCRT. Compared with CCRT alone, CCT following CCRT improved overall survival (OS) (HR 0.72; 95% CI, 0.59–0.86, p < 0.001) and progression-free survival (PFS) (HR 0.61; 95% CI, 0.44–0.84, p=0.003), but did not improve disease control rate (DCR) (OR 1.66; 95% CI, 0.53–5.15, p=0.384) and objective response rate (ORR) (OR 1.44; 95% CI, 0.62–3.35, p=0.393). The risk of treatment toxicity was not increased for EC patients who received CCT. Conclusion CCT followed by CCRT significantly increased OS and PFS of non-surgical esophageal cancer patients and may provide them remarkable survival benefit. The results offer an evidence-based framework for the use of consolidation chemotherapy after concurrent chemoradiotherapy.